Análise da influência do sistema de outrigger no projeto de edifícios altos em concreto armado no Brasil - Piccoli, Vitória da Cunha (2023)
The construction of tall buildings has emerged as a response to the scarcity of horizontal space in major urban centers. Wind action is a significant concern in the structural design of these buildings, given its generation of substantial displacements. Therefore, the choice of lateral bracing system directly influences the technical and economic feasibility of constructing such tall buildings. This study focuses on one such system, outriggers. These comprise walls or beams of high rigidity, positioned on specific floors, connecting the core to the exterior frame. The objective of this research is to analyze the influence of this system on the global stability of tall reinforced concrete buildings in Brazil. For this purpose, parameters influencing global stability are evaluated, namely: the basic wind speed V0 (30, 40, and 50 m/s); the characteristic concrete strength fck (30, 40, and 50 MPa); and the stiffness of beams simulating this system through variation in their sections (40, 60, and 80 cm). Using an initial structural configuration with a typical floor size of 15x25m and a height of 150m, 15 buildings were modeled in TQS® software full version LVP&S v23, provided by the company. The model was processed and resized to meet the instability parameter ᵞz ≤ 1.10. Following this assessment, the defined parameters were incorporated, and the results were compared in terms of the base moment of the core and the total horizontal displacement at the top of the building. In models where the outrigger system is present, three floors are braced by the system using beams of high rigidity positioned optimally based on the location of outriggers. It is concluded that the inclusion of the outrigger system significantly reduces horizontal displacements at the top of the structure and flexural moment stresses at the base of the rigid core. Quantitatively, this reduction exhibited rates between 6% and 8% for the direction of lesser rigidity and greater wind influence (90°), and between 1% and 3% for the 0° direction. Additionally, the system performed better for models with higher values of basic wind speed, wider outrigger beam sections, and intermediate fck of 40 MPa.